Application of Hydraulic Drawing Device of Belt in Laying and Retraction of Steel Belt - LI Ju-peng; ZHANG Hong-kui; HE Ru-yi; GUO Yao-we (Gong-kuang zidonghua, 2010)
In view of problems of difficult work, more man and material resources required and no high safety factor, the paper designed a hydraulic drawing device of belt, and introduced the composition and working principle of the device. It also introduced the application of the device in upward belt conveyor with high inclination-angle in No.3 mining area of Xinbai Coal Mine. The device improves safety and reliability of laying and retraction of steel belt, enhances working efficiency and lightens labor intensity of operation personnel.